Implementation Strategy of Higher Education Social Responsibility to Acquire New and Qualified In-Line Students: A Case Study - Nung Harjanto; Rahmawati Rahmawati; Hasan Fauzi; M. Agung Prabowo (Universitas Pasundan, 2019)
This study aims to provide novel empirical evidence about the effectiveness of higher education social responsibility (HESR) as a strategy to acquire new and qualified in-line students for higher education institutions. In this research, a case study of Akademi Akuntansi YKPN Yogyakarta, a leading higher education institution offering vocational accounting courses in Indonesia, is used. Results show that the number of HESR activities implemented in vocational higher education has positive significant effects on new and qualified in-line students. Our hypothesis tested through linear regression also reveals that the number of HESR activities implemented in vocational higher education positively affects the number of its new and qualified in-line students from related partner vocational high schools. This research contributes to the analysis of supply chain linkage literature, especially linkages for higher education institutions, through the implementation of HESR as a strategy to acquire these students in higher education institutions and to achieve a sustainable competitive advantage. Although this topic in higher education is important, it has been rarely explored.